Model Test on Bearing Characteristics of Basalt Fiber-Reinforced Concrete Lining - Dao-yuan Wang; Jia-suo Qi; Guang-yao Cui; Yanling Yang; Jie Chang (Advances in Materials Science and Engineering)
Adding fiber can improve the brittleness of plain concrete. Compared with plain concrete, basalt fiber-reinforced concrete has the advantages of strengthening, toughening, and crack resistance. Compared with steel fiber-reinforced concrete, basalt fiber-reinforced concrete has better construction performance. Basalt fiber concrete is a type of inorganic material with environmental protection and high mechanical properties, which has an important mechanical advantage for controlling the deformation of the soft surrounding rock tunnel. Through the indoor model test of mechanical behavior of reinforced concrete and basalt fiber-reinforced concrete lining, the bearing characteristics of basalt fiber-reinforced concrete lining was studied. The results show that, compared with reinforced concrete, the initial crack load of basalt fiber-reinforced concrete is increased by 20%; the toughness of lining structure is enhanced by adding basalt fiber, and the lining can still bear large bending moment and deformation after the initial crack appears; after the initial crack appears, the bearing characteristic curve of reinforced concrete lining rises slowly and converges rapidly; the bearing characteristic curve of basalt fiber-reinforced concrete lining rises slowly, and there is no sign of convergence when it reaches 2 times of initial crack load. For the soft surrounding rock tunnel, it is necessary to seal the rock surface as early as possible, provide support as soon as possible, and have a certain deformation capacity. Basalt fiber-reinforced concrete can better meet these needs.